1994
DOI: 10.1227/00006123-199402000-00010
|View full text |Cite
|
Sign up to set email alerts
|

Management of Neurosurgical Patients with Hyponatremia and Natriuresis

Abstract: The main objective of our study was to evolve a practical management protocol for neurosurgical patients with hyponatremia and natriuresis, based on their blood volume status and hematocrit. Twenty-one patients with hyponatremia and natriuresis and 3 control patients were studied. Patients with hyponatremia were categorized on the basis of their hematocrit, central venous pressure, and total blood volume. Group A consisted of patients with hypovolemia and anemia (16 patients); Group B patients had hypovolemia … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
47
0
4

Year Published

1997
1997
2018
2018

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 120 publications
(52 citation statements)
references
References 23 publications
1
47
0
4
Order By: Relevance
“…the incidence of csWs among all the patients was greater than that of sIADH, which is in agreement with reports from various other authors, who also observed a greater prevalence of csWs, compared to sIADH in neurological patients 1,2,4,5,10,18,30 . the coexistence of DI and csWs (mixed syndrome) observed in our patients has also been described by yamaki et al 17 , who studied two patients postoperatively following surgery for pituitary tumor and observed the presence of severe natriuresis and hyponatremia in a study patient who developed DI (fluid loss >2.36 ml/kg/h), which led the authors to conclude that hyponatremia resulting from csWs in intracranial diseases may develop in patients with DI.…”
Section: Discussionsupporting
confidence: 93%
See 4 more Smart Citations
“…the incidence of csWs among all the patients was greater than that of sIADH, which is in agreement with reports from various other authors, who also observed a greater prevalence of csWs, compared to sIADH in neurological patients 1,2,4,5,10,18,30 . the coexistence of DI and csWs (mixed syndrome) observed in our patients has also been described by yamaki et al 17 , who studied two patients postoperatively following surgery for pituitary tumor and observed the presence of severe natriuresis and hyponatremia in a study patient who developed DI (fluid loss >2.36 ml/kg/h), which led the authors to conclude that hyponatremia resulting from csWs in intracranial diseases may develop in patients with DI.…”
Section: Discussionsupporting
confidence: 93%
“…Alterations in sodium are frequently found in neurological and neurosurgical patients [1][2][3][4][5][6][7] and are associated with alterations in the osmolarity of the extracellular medium and changes in the volume of the cells of the central nervous system (cNs). they may aggravate the condition of these patients 8 .…”
mentioning
confidence: 99%
See 3 more Smart Citations